The effects of radical prostatectomy on gay and bisexual men's sexual functioning and behavior: qualitative results from the restore study. Issue 4 (1st October 2016) - Simon Rosser, B.R.; Capistrant, Benjamin; Torres, Maria Beatriz; Konety, Badrinath; Merengwa, Enyinnaya; Mitteldorf, Darryl; West, William
ABSTRACT: To advance research on the sexual effects of prostate cancer in sexual minorities, we conducted telephone interviews with 19 gay and bisexual men (GBM) who had undergone radical prostatectomies. Challenges to sexual functioning included anatomical penile changes, loss of ejaculate, climacturia, and erectile dysfunction. All sexual behavior with other men, not just insertive anal sex, was affected, across all stages of the sexual response cycle. Rather than narrowly focusing on erectile functioning, rehabilitation for GBM needs to be comprehensive in addressing anatomical changes, sexual behavior comprehensively, and functioning across the sexual response cycle. Seven recommendations for practitioner education are identified.